Superparamagnetismo em Jacobsitas sintéticas - Barbosa, Mateus Bruno (2012)
In this experimental study sintetic samples of Jacobsites (MnFe2O4) were synthesized by the Pechini method and calcined within ambient atmosphere and afterwards in the vacuum from 400 to 700ºC, the range of calcination temperatures. The X-Ray Diffraction (XRD) and the Scanning Electronic Microscopy (SEM) analysis have shown that the samples treated at 400ºC temperature are composed by a simple type of spinel phase, with a crystallite size of 8:8nm for the sample calcined in ambient atmosphere and 20; 1nm for the sample treated in the vacuum, showing that the cristallite average size can be manipulated by the atmosphere control. The hysteresis loops for the sample calcined at 400ºC in ambient atmosphere reveal features of superparamagnetic behavior with magnetization 29:3emu=g at the maximum field of 1:2T. The sample calcined in 400oC under vacuum show magnetization = 67emu=g at the maximum field of 1:5T. The sample treated at 500oC, under ambient atmosphere, has shown besides the spinel phase, secondary phases of hematite (Fe2O3) and bixbyite (FeMnO3). The hysteresis loops demonstrate a sharp drop of the magnetization compared to the previous sample. The analysis has revealed that for the samples treated in higher temperatures (600ºC and 700ºC) its observed the absence of the spinel phase and the maintenance of the bixbyite and hematite. The hysteresis loops for those samples in accordance to the external magnetic field are straight lines crossing the origin, consistent with the antiferromagnetic behavior of the phases.The Mössbauer espectroscopy show to the sample calcined at 400ºC within ambiente atmosphere two sextet and one doublet. The two sextets are assigned to the hyperfine fields related to the magnetic deployment in the nuclei of Fe3+ ions, at the tetraedric and octaedric sites. The doublet is assigned to superparamagnetic behavior of the particles with smaller diameter than dc . Now the sample calcined at 400ºC under vacuum only show two sextet